(untitled) (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
Review of R.W. Redding (ed.), A View from the Herd. Cattle, Sheep, Goats, and Pigs in Pharaonic Egypt. A Primer for Egyptologists and Archaeologists (Archaeobiology V), Lockwood Press, Columbus (GA) 2024, 190 p, Paperback - 69.95, ISBN: 978-1-957454-08-5